2007
DOI: 10.1016/j.biocel.2006.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Ntal/Lab/Lat2

Abstract: NTAL (non-T cell activation linker)/LAB (linker for activation of B cells), now officially termed LAT2 (linker for activation of T cells 2) is a 25-30 kD transmembrane adaptor protein (TRAP) associated with glycolipid-enriched membrane fractions (GEMs; lipid raft) in specific cell types of hematopoietic lineage. Tyrosine phosphorylation of NTAL/LAB/LAT2 is induced by FcεRI aggregation and Kit dimerization in mast cells, FcγRI aggregation in monocytes, and BCR aggregation in B cells. NTAL/LAB/LAT2 is also expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…SH2 domain containing leukocyte protein of 76 kDa is needed for FcgR-mediated ROS production in neutrophils (13), but not in macrophages (14,15), which may be because of differential FcgR expression. Linker for activation of T cells (LAT) and LAT2 can be phosphorylated by Syk and Src kinase Lyn (16,17) and have been shown to be critically involved in myeloid ITAM signaling (18)(19)(20). It has been suggested that FcgRI, but not FcgRIIa, cross-linking leads to phosphorylation of LAT2 in the human monocytic cell line THP-1.…”
Section: Fcgri Downstream Signalingmentioning
confidence: 99%
“…SH2 domain containing leukocyte protein of 76 kDa is needed for FcgR-mediated ROS production in neutrophils (13), but not in macrophages (14,15), which may be because of differential FcgR expression. Linker for activation of T cells (LAT) and LAT2 can be phosphorylated by Syk and Src kinase Lyn (16,17) and have been shown to be critically involved in myeloid ITAM signaling (18)(19)(20). It has been suggested that FcgRI, but not FcgRIIa, cross-linking leads to phosphorylation of LAT2 in the human monocytic cell line THP-1.…”
Section: Fcgri Downstream Signalingmentioning
confidence: 99%
“…LAT2 is a transmembrane adaptor in specific cell types of hematopoietic lineages. Functional studies have indicated that LAT2 plays a putative role as regulator of mast cell activation, but its defined role in the organism remains unclear [176].…”
Section: The Single Copy Gene Part Of the Wbs Regionmentioning
confidence: 99%
“…Cbl proteins containing several protein modulatory regions and most notably a ring finger domain that functions as an E3 ligase in the ubiquitation and rapid down-regulation of various receptors including the EGF, PDGF, T and B cell receptors [82][83][84][85]. However, the insulin receptor does not undergo a rapid down-regulation process following ligand engagement in contrast to these other receptors.…”
Section: Insulin Signaling Leading To Glut4 Translocationmentioning
confidence: 99%